ESTABLISHMENT OF CONNECTIONS BETWEEN HYDROGEOPHYSICAL AND WATERPHYSICAL PARAMETERS OF ENVIRONMENT FOR SOLVING GEO-ECOLOGICAL PROBLEMS (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
In the article problems of establishment of correlation connections between hydrogeophysical and waterphysical characteristics of volcanic formations are examined. These connections are based on well-known analogue between geoelectrical and hydrodynamical parameters. The results of the studies are used for solving geo-ecological problems in connection with estimate of groundwater flows' charges and determination of permissible reductions during the exploitation of groundwaters in volcanic regions.
Keywords: hydrogeophysical and waterphysical methods; belt of regional fracturing